Pengaruh intensitas naungan terhadap morfologi dan warna daun Aglaonema commutatum ‘Siam Aurora’ - Afifah, Ulil Azmi Nurlaili; Rusmiyati, Henny; Kartiman, Roni; Manalu, Doni Sahat Tua; Tirtana, Arif; Marithasari, Harries (JURNAL AGRONIDA, 2025)
Aglaonema ‘Siam Aurora’ is a foliage ornamental plant cultivar commonly used indoors, whose leaf coloration is influenced by shade levels. This study aimed to determine the effect of shade intensity on the vegetaitif and morphological changes of Aglaonema ‘Siam Aurora’. The experiment was arranged in a Randomized Complete Block Design (RCBD) with four treatments: control (no shade), and shading using 55% paranet in one, two, and three layers. Observations were made on changes in leaf and stem color using the RHS Colour Chart, as well as on plant morphological growth. The results showed that shading had no significant effect on plant height, leaf length, and leaf width, but significantly affected the number of leaves during weeks 6 to 8. The color of the center and edges of the leaves developed optimally under all treatments, indicating the plant's physiological adaptation to low light conditions. Stem color differed in the early stages but tended to become uniform by week 8. Leaf shape showed initial variation but became uniform after the fifth week. These findings suggest that Aglaonema ‘Siam Aurora’ has high tolerance to low to moderate light intensity, and shading with one to two layers of 55% paranet is effective in maintaining leaf morphology and color. More extreme shading levels and longer planting durations are recommended to further explore morphological responses.